Cutaneous reflex modulation and self-induced reflex attenuation in cerebellar patients - Hoogkamer, Wouter (J Neurophysiol, 2014)
Modulation of cutaneous reflexes is important in the neural control of walking, yet knowledge about underlying neural pathways is still incomplete. Recent studies have suggested that the cerebellum is involved. Here we evaluated the possible roles of the cerebellum in cutaneous reflex modulation and in attenuation of self-induced reflexes. First we checked whether leg muscle activity during walking was similar in patients with focal cerebellar lesions and in healthy control subjects. We then recorded cutaneous reflex activity in leg muscles during walking. Additionally, we compared reflexes after standard (computer triggered) stimuli with reflexes after self-induced stimuli for both groups. Biceps femoris and gastrocnemius medialis muscle activity was increased in the patient group compared with the control subjects, suggesting a coactivation strategy to reduce instability of gait. Cutaneous reflex modulation was similar between healthy control subjects and cerebellar patients, but the latter appeared less able to attenuate reflexes to self-induced stimuli. This suggests that the cerebellum is not primarily involved in cutaneous reflex modulation but that it could act in attenuation of self-induced reflex responses. The latter role in locomotion would be consistent with the common view that the cerebellum predicts sensory consequences of movement.